Predator Prey Interaction on some Wheat Cultivars - S. Shahzad Ali; Sakhawat Ali; Syed Sohail Ahmed; Huma Rizwana; Shahnaz Naz; Falaknaz Meano; Paras; Sumbul; Sher Ahmed (Journal of Basic & Applied Sciences, 2016)
The present findings was aimed to determine the predator prey interaction on some wheat cultivars was laid out at Experimental Area of Entomology Section, Agriculture Research Institute, Tandojam during rabi wheat growing season of 2014. Five wheat varieties were sown in a complete randomized block design plot. The varieties are 1. NIA-Sunhari, 2. NIA-Amber, 3. NIA-Sundar, 4.Kiran 5.Kirman.The results indicated that maximum mean population of insect pest and predators were recorded on different varieties of wheat crop. The maximum mean Black aphid population was recorded on variety of NIA-Amber (3.36/leaf) and minimum on Kiran (2.79/leaf). The maximum mean numbers of green aphids were recorded on variety Kiran (5.26/leaf) and minimum mean population on variety NIA-Amber (3.59/leaf). The maximum American bollworm was recorded on variety of NIA-Sunhari, (0.51/leaf) and minimum population was recorded on variety NIA-Sundar (0.14/leaf). Its population was increase in the mid to end of season. The maximum Thrips population appeared on variety NIA-Amber (5.61/leaf) and lowest on NIA-Sunhari (2.79/leaf). The Thrips increased slowly at the start of the season and continued at mid to end of the season. Among predators, the maximum population of Brumus was recorded on variety NIA-Sunhari (0.81/plant) and lowest population observed on variety of NIA-Sundar (0.05/ plant). Similarly the lacewing was recorded on variety of NIA-Sunhari (0.25/plant) and its lowest population was on varieties of Khirman and Kiran (0.05/plant). Maximum 7- spotted beetles population was on variety NIA-Sunhari (0.64/plant) and the lowest population on Kiran (0.15/plant). While the maximum mean population of 11- spotted beetles was recorded on variety of NIA-Sunhari (0.52/plant) and the minimum population on Kiran (0.17/plant).